Epineurectomy of Facial Nerve Trunk for Refractory Oral-Ocular and Oculo-Oral Synkinesis Following Bell Palsy. Issue 8 (November 2021) - Wei, Xiangyu; Chang, Bowen; Li, Shiting
Abstract : Background: Synkinesis is a common sequelae after incomplete recovery from Bell palsy. Current first-line treatments include botulinum toxin injection and physical therapy. However, patients unresponsive to these treatments may require further surgery. Various surgical treatments have been reported, but no consensus has been reached for the optimal surgery. In a guinea pig model of synkinesis, the facial nerve trunk (FNT) was observed using a scanning electron microscope. Based on the results of scanning electron microscope and clinical ultrasonography, the authors chose FNT as the therapeutic target. Methods: The authors performed epineurectomy of FNT for 11 patients with refractory oral-ocular and oculo-oral synkinesis under abnormal muscle response and facial electromyography monitoring. The postoperative assessments at 1 year were conducted using Sunnybrook Facial Grading System and Facial Disability Index scale. Furthermore, the epineurium excised during the operation was collected as the specimen and submitted for histopathological examination; the cadaveric FNT served as the control group. Results: The follow-up results showed significant relief from synkinesis (4.91 ± 0.37 versus 10.18 ± 0.64, P < 0.01), improvement of physical (84.55 ± 1.96 versus 73.18 ± 3.65, P < 0.01) and social functions (77.09 ± 3.24 versus 61.82 ± 6.28, P < 0.01), with no worsening of facial paralysis in the patients. The histopathological examination revealed many nerve fibers in the epineurium, suggesting that FNT was the area of aberrant axon regeneration. Conclusions: Epineurectomy of FNT is a safe and effective surgical remedy. It can be considered as a surgical option for patients with refractory oral-ocular and oculo-oral synkinesis following Bell palsy. Abstract : Supplemental Digital Content is available in the text